Atitudes de professores sobre o TDAH e sobre estudantes com sintomas de TDAH - Oliveira, Mônica Santos (2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder with a worldwide prevalence of 7.2%. It is characterized by a constant pattern of inattention, hyperactivity and impulsivity that interfere with the development and functioning of the child. ADHD begins in childhood and, for its diagnosis, it is necessary that a series of symptoms are present until the child's 12 years of age. In general, teachers are the first to notice the symptoms of ADHD in children due to their behaviors and/or poor school performance due to difficulty in attention. Therefore, the objective of this study was to evaluate the attitudes of teachers towards ADHD and children with ADHD-type behaviors. For this, the participating teachers answered an adapted questionnaire with questions about attitudes towards ADHD, knowledge of ADHD, need for knowledge and need for development, as well as a sociodemographic questionnaire. Data analysis was performed with a quantitative approach with emphasis on factor analysis and structural equation modeling. The results showed that teachers have positive attitudes toward ADHD and children with ADHD-like behaviors and that knowledge about ADHD is the factor that most impacts attitudes about ADHD, along with knowledge and development needs.